Predictors of mothers' postpartum body dissatisfaction based on demographic and fertility factors - Mehrri Tavakoli; Seyedeh Batool Hasanpoor-Azghady; Leila Amiri Farahani (BMC, 2021)
Abstract Background There are fundamental and rapid changes in body shape during pregnancy, some of which persist for an extended time after delivery and may cause dissatisfaction with body shape. Therefore, we conducted this study to determine predictors of body dissatisfaction at six months postpartum based on demographic and fertility factors. Methods This cross-sectional study was conducted on 300 women who referred to seven health centers affiliated with Iran University of Medical Sciences, Tehran, Iran. The sampling was multistage and we collected data from a demographic and fertility questionnaire and Cooper's Body Shape Questionnaire (BSQ-34). The independent t-test, Mann-Whitney U test, chi-square test, one-way ANOVA, Kruskal-Wallis, Pearson correlation coefficient, and multiple linear regression were used for data analysis. The level of significance was set at P < 0.05. Results The mean age of participating women was 29.77 (standard deviation: 5.9) years. Body dissatisfaction had a statistically significant association with variables such as body mass index (BMI) at six months postpartum, gestational age, the receipt of information about body shape, spouse's views on the shape of a woman's body, and mode of delivery. These variables predicted 34% of body dissatisfaction based on multiple linear regression. Conclusion Postpartum body dissatisfaction is related to a several variables. Paying attention to these variables will help to plan and improve postpartum counseling and educational programs.